2023
DOI: 10.3389/fevo.2023.1151001
|View full text |Cite
|
Sign up to set email alerts
|

The impact of freezing on the post-mortem human microbiome

Abstract: IntroductionHuman donations are often used in forensic research as they can provide unique insights into post-mortem research that cannot be obtained with animal proxies. This is especially true for forensic microbiome research, as human circumstances such as drug-use or health conditions may influence the post-mortem microbiome. However, it is not always feasible to conduct such research immediately after death. Donors are often stored frozen in human taphonomy facilities, pending the start of any experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…In our investigation, Actinobacteria and Firmicutes slightly decreased over the first 12 h, while Bacteroidetes and Proteobacteria increased. In previous studies Firmicutes was found to be a constant marker between different body areas ( Roy et al, 2021 ), while this phylum and Proteobacteria were found to be the predominant taxa identified from buccal swabs collected from cadavers in different decomposition stages ( Sguazzi et al, 2022 ; Ogbanga et al, 2023 ). The increase in Bacteroidetes is in contrast with previous findings ( Pechal et al, 2018 ), however, the sampling areas must be taken into consideration (face and hands vs. eyes, nose, mouth).…”
Section: Discussionmentioning
confidence: 90%
“…In our investigation, Actinobacteria and Firmicutes slightly decreased over the first 12 h, while Bacteroidetes and Proteobacteria increased. In previous studies Firmicutes was found to be a constant marker between different body areas ( Roy et al, 2021 ), while this phylum and Proteobacteria were found to be the predominant taxa identified from buccal swabs collected from cadavers in different decomposition stages ( Sguazzi et al, 2022 ; Ogbanga et al, 2023 ). The increase in Bacteroidetes is in contrast with previous findings ( Pechal et al, 2018 ), however, the sampling areas must be taken into consideration (face and hands vs. eyes, nose, mouth).…”
Section: Discussionmentioning
confidence: 90%
“…Two more studies based on an Italian sample composed of oral and skin microbiomes on 50 subjects showed a positive relationship between the abundance of Spirochaetota and Synergistota and the age of the enrolled participants [235,303].…”
Section: Search Resultsmentioning
confidence: 98%
“…Pechal et al [234] showed a shift in the post-mortem microbial communities (structure and abundance) during the thawing process of two pediatric cases, whereas Ogbanga et al [235] showed that storing bodies frozen preserves the composition and abundance of their pre-freezing microbiome despite reporting some statistically nonsignificant changes to the post-mortem microbiome post freezing and thawing. These results, despite limited to a few studies, highlight the needs for a better understanding of the effects that storage conditions can have on the bodies, to ensure a correct interpretation of the findings for the identification of potential biomarkers for PMI estimation and human profiling.…”
Section: Microbiomics For Pmi Estimationmentioning
confidence: 99%